Americas Start-Ups – Inspiration for a Copycat in Europe? - Klijer, Sven; Lukeš, Martin, 1976-; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This thesis recognizes the opportunity that stems from start-ups in America and a potential launch of copycat companies in Europe. It describes important factors for start-ups and copycats. Based on the industries of the fastest-growing companies in America, certain industries are picked for further exploration. Two ideas from the “E-Commerce” and “Sales & Marketing” industry are thoroughly analyzed. The analysis aims to answer the feasibility of a potential launch of a copycat model in the European market. Based on extensive market research and interviews with investors in Europe a final assessment is developed. Both companies would face different severe challenges that make a market launch in Europe unfeasible. Therefore, the investigated business ideas from the US market cannot serve as an inspiration for founders in Europe.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses